Implementation of the Living Pharmacy Program as an Effort to Educate Health and Preserve the Environment - Nurul Ifpah; Rifka Romiantika Annisa; Dwiyana Putriani; Baiq Ulya Innayatussoliha; Lalu Ezi Zuddin; Winardi Mirfa; Zalia Muspita (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The Living Pharmacy Program at State Elementary School 1 Keroya was implemented with the aim of increasing students' understanding of the importance of health and environmental preservation through the use of medicinal plants. This program aims to provide education to students on how to plant, care for, and utilize medicinal plants as an environmentally friendly alternative to natural medicine. In addition, this activity also aims to foster student awareness in maintaining biodiversity and supporting environmental conservation through the sustainable use of natural resources. The implementation of the program involves various parties, including teachers, students, and the surrounding community who participate in the learning process as well as direct practice at school. The results of this program showed an increase in students' knowledge about the benefits of medicinal plants and the important role of plants in maintaining the balance of the ecosystem. In addition, this program succeeded in shaping the character of students who care about health and the environment. The Living Pharmacy program is expected to be an educational model that can be applied in other schools as part of efforts to improve the quality of health and a better environment in the future.